2016
DOI: 10.1007/978-1-4939-3130-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx Remodeling with Glycopolymer-Based Proteoglycan Mimetics

Abstract: The cellular glycocalyx controls many of the crucial signaling pathways involved in cellular development. Synthetic materials that can mimic the multivalency and three-dimensional architecture of native glycans serve as important tools for deciphering and exploiting the roles of these glycans. Here we describe a chemical approach for the engineering of growth-factor interactions at the surfaces of stem cells using synthetic glycomimetic materials, with an eye towards promoting their commitment towards specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…To determine the GAG specificity for stimulating matrix assembly, we used synthetic GAG-mimetics that represent naturally occurring HS sulfation motifs [28, 29]. These GAG-mimetics are synthesized by attaching disaccharides with varying degrees of sulfation to ligation sites along a soluble linear polymer of fixed length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the GAG specificity for stimulating matrix assembly, we used synthetic GAG-mimetics that represent naturally occurring HS sulfation motifs [28, 29]. These GAG-mimetics are synthesized by attaching disaccharides with varying degrees of sulfation to ligation sites along a soluble linear polymer of fixed length.…”
Section: Resultsmentioning
confidence: 99%
“…In the heparin mimetic D2S6, disaccharides were triple-sulfated whereas D2A6 resembled HS in having two sulfates per disaccharide, and D0A0 was unsulfated (Fig. S3A) [28, 29]. The main advantage of using synthetic GAG-mimetics is that, unlike natural HS or heparin, all of the GAGs in a mimetic have identical numbers of sulfates and sulfation patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Membraneassociated (green) fluorescence was observed in cells treated with ManNAz at all polymer concentrations used, in a dosedependent manner. The absence of polymer-associated fluorescence in control cells (no ManNAz) confirmed that "click" conjugation occurred, rather than nonspecific mechanisms (such as membrane insertion) 47 or cellular uptake (endocytosis).…”
Section: Acs Macro Lettersmentioning
confidence: 80%
“…As previously discussed, hydrophobic insertion of polymers provides a noninvasive, simple, and cytocompatible approach to introduce functionality and has been used to probe and modulate the functional importance of the glycocalyx with synthetic polymers. 23,79 However, passive insertion of lipidbased polymers is limited by rapid dissociation times, with lipid-glycoconjugates possessing a surface half-life of 4−8 h 79 and the complete dissociation of the synthetic PEG-lipid occurring within 3 h due to intrinsic membrane turnover processes, Figure 3B. 89,105 Synthetic polymers installed onto exogenous azide receptors produce robust covalent linkages that survive multiple mitotic divisions, with the cell-surface bound polymer remaining beyond 3 days, a similar time scale compared to polymer−protein conjugation approaches, 20 and the cell surface bound polymer is passed onto daughter cells.…”
Section: Conventional Versus Metabolic Approaches For Polymer Recruit...mentioning
confidence: 99%
“…24 Godula and co-workers revealed that lipidated synthetic neoproteoglycans, mimetics of native sulfated glycosaminoglycans (HS GAGs), can recruit fibroblast growth factor 2 (FGF2) to induce neural specification downstream signaling pathways in embryonic stem cells (ESCs) deficient in exostosin, a key glycotransferase enzyme required for native HS GAGs assembly. 79 Similarly, rat cortical neurons engineered with chondroitin HS GAG conjugated liposomes, for membrane fusion, have been used to enhance nerve growth factor-mediated signaling and promote neural outgrowth in rat cortical neurons by activating neurotrophin-mediated signaling pathways. 23 Metabolic recruitment of synthetic polymers: Although reengineering cellular interfaces has huge potential for cell-based therapies, targeting endogenous cell membrane components presents challenges limiting its translational application including cytotoxicity, short membrane retention time, and lack of specificity.…”
mentioning
confidence: 99%